PENINGKATAN KINERJA GURU MELALUI KEGIATAN PELATIHAN PENYUSUNAN PROPOSAL PENELITIAN TINDAKAN KELAS (PTK) (STUDI KASUS PADA GURU – GURU EKONOMI DI KABUPATEN MALANG) - Sri Handayani; Nasikh Nasikh; Annisya’ Annisya’ (Jurnal Pendidikan Ekonomi, 2017)
The performance of professional teachers should be owned by every educator because through these conditions can be obtained education that can form a quality human. One of the things that should be done by teachers to have professional performance must be able to prepare a Classroom Action Research Proposal (PTK). The main purpose of TOD is to improve and improve the professional services of teachers. Objectives to be achieved in this research are: 1) To improve the competence of preparing classroom action research proposal (PTK) economic teachers in Malang Regency, 2) To know the effectiveness of preparation of PTK proposal for economic teachers in Malang Regency. DOI: https://dx.doi.org/10.17977/UM014v10i22017p183